High-Performance Neuroprosthetics: Improvements within Reach - Rizzo, Toni (MD Conference Express, 2014)
This article discusses the development of high-performance neuroprosthetics, including a broad perspective of how the brain functions during volitional movement, and how neuron signals can be recorded and the information used to direct movement of a prosthetic arm.